We can factor the denominator as the difference of squares:
a^2 - 1 = (a + 1)(a - 1).
Then we can rewrite the fraction as:
2(a + 1)(a - 1) / [(a + 1)(a - 1)]
The (a + 1)(a - 1) terms cancel out, leaving us with:
2
Therefore, the simplified form of the expression is 2.
Simplify. start fraction 2 a plus 2 over a squared minus 1 end fraction
2 answers
trying to decode : start fraction 2 a plus 2 over a squared minus 1 end fraction
assuming you meant (2a + 2)/(a^2 - 1)
= 2(a + 1)/( (a + 1)(a - 1) )
= 2/(a - 1) , a ≠ ± 1
assuming you meant (2a + 2)/(a^2 - 1)
= 2(a + 1)/( (a + 1)(a - 1) )
= 2/(a - 1) , a ≠ ± 1